Analysis of News Item Text Found In â€œAntara Newsâ€ Entitled: â€œIndonesian Police Re-Examine â€˜plasticâ€™ riceâ€ - Didi Hermawan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Antara News is one of the daily English newspaper which is oriented in some various field such as headline, editorial, article, opinion, world and etc. This paper aims to analyse the news item text in Antara News entitled â€œIndonesian Police Re-Examine â€˜plasticâ€™ riceâ€. Â The object of this study is news taken from Antara NewsÂ  online Â published on 26th of may 2015, 15:56:55 pm. In this study, the writer concerned on functional grammar, mainly on ideational meaning. In order to get the objective of this study, the writer used some theories related to the literature, discourse, genre, grammar and ideational meaning itself. In the Process type analysis, there were four types of processes found in the news and the most process appeared was material process. The writer also found that there was news item genre, instead of recount, which dominate the text . the recount or past tense develop the text